Effect of Vitamin E on Human Periodontal Ligament Fibroblasts - Maurtgi, Moustafa; Mohamad, Sharlina binti; Mohd Noor, Siti Noor Fazliah; Mokhtar, Norehan (AIP Publishing, 2016)

(untitled)
The periodontal ligament fibroblasts plays an essential role in the organization and maintenance of the connective tissue during development and in response to injuries and diseases. They are also responsible of the migration and differentiation of the variety of cells that takes part in the osteogenesis in response to external forces (1, 2). Age related changes include decreased fibroblasts density and cellular activity which slows orthodontic tooth movement due to prolonged response of the connective tissue to external forces which poses a potential risk in orthodontic treatment (3, 4). Vitamin E had been studied worldwide due to its health benefits in the fields of chronic diseases and ageing such as the anti-inflammatory and anti-osteoporotic effects (5, 6). Vitamin E consists of 2 major isoforms: tocopherols and tocotrienols, each with four distinct analogues (alpha, beta, gamma, and delta). Tocopherols are saturated forms of vitamin E, and tocotrienols are the unsaturated forms, distinguishable by the three double bonds in the tails of tocotrienols (7). Studies showed that tocotrienol is superior for its antioxidant properties as well as increasing cells viability and proliferation (8, 9). The current project aim to evaluate the response of human periodontal ligament fibroblasts (HPdLF) upon exposure to various concentrations of tocotrienols rich fraction (TRF) conditioned medium.